Hydrauliken i Ångersjöns fosforfällor - Jansson, Ellinor (2008)
Discharge of untreated wastewater leads to unnaturally high levels of nitrogen and phosphorus in rivers, lakes and the sea, which results in unbalanced ecosystems with eutrophication and lack of oxygen. Part of the phosphorus in surface waters is coming from on-site wastewater treatment from scattered households with unsatisfactory purification.